An Analysis of Economic Growth Led Urbanization of Jalalabad Town: - (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The present paper studies town Jalalabad (west),District Fazilka, Punjab. Its urbanization is related with Market Forces andGovernment Policies. Growth of town with tertiary and secondary economicactivities since 1991 has been taken into consideration.